Evaluation and Management of Lateral Ankle Pain Following Injury. Issue 8 (August 2018) - Lau, Brian C.; Moore, Laura K.; Thuillier, Daniel U.
Abstract : Ankle sprains are the most common disorder in patients with lateral ankle pain; however, other pathologies can present similarly and can require different treatments. In the acute setting, it is important to evaluate for subtle fractures that may mimic an ankle sprain, including fractures of the lateral process of the talus, anterior process of the calcaneus, or base of the fifth metatarsal. In addition, ankle sprains may also involve further injury to the syndesmosis (high ankle sprains), articular cartilage (osteochondral lesions), or peroneal tendons. Proper diagnosis through physical examination and appropriate imaging can help to ensure proper treatment. It is important to consider that multiple causes of lateral ankle pain can coexist, particularly in cases of chronic lateral ankle pain.